PENINGKATAN PENGETAHUAN KESEHATAN GIGI DAN MULUT, PENURUNAN KARIES DAN PENINGKATAN CAKUPAN PENAMBALAN/PERAWATAN GIGI PADA MASYARAKAT DI BANTARAN SUNGAI MARTAPURA - Said, Fahmi bin; Rahmawati, Ida; Isnawati, Isnawati (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2023)
Caries is a disease that is still a major problem in the field of dental health in the world, including in Indonesia. Various efforts must continue to be made to reduce the incidence of caries, both promotive and preventive, as well as curative and rehabilitative. The DMF-T index in Banjar Regency is 7.8 with D-T=1.62, M-T=5.88, and F-T=0.34 and is one of the districts that has a DMF-T value above the index for South Kalimantan province. The results of the 2016 Banjar District Health Service survey stated that the highest number of permanent tooth fillings and extractions was in Martapura District with a total of 1148 permanent tooth fillings and 895 permanent tooth extractions. Community service aims to increase knowledge of dental and oral health and brushing skills, increase PTI rates and reduce dental caries rates in the community in Pekauman village, Banjar Regency, East Martapura District on the Martapura River. The method used is analytical observational with a cross sectional approach. The community service population is the people of Pekauman Village, Banjar Regency, East Martapura District on the the Martapura River. As a result of community service, there was an increase in knowledge about dental health from an average of 52.40 high criteria to very high 83.27. The achievement of reducing the number of dental caries by 27.43% and increasing the Performance Treatment Index (PTI) number was achieved from 3.6% to 23%. Keywords: Knowledge, dental caries rates, PTI rates